(untitled) (Journal of Environmental Microbiology and Toxicology, 2024)
Malachite green (MG) is still used at present to cure fish and prawn that have been infected with pathogenic agents in aquaculture and the ornamental fish sector. It is most used for its antifungal, antiparasitic, and antibacterial activities. The therapeutic and lethal dose is also fairly close, and there is a risk of overdoes when used for treatment. Moreover, MG is also emitted into the environment through the disposal of effluents from aquaculture farms, which may lead to aquatic environments being polluted. This study aimed to establish a method of detection of Malachite Green (MG) in environmental samples using solid phase extraction in conjunction with visible spectrophotometry. The calibration curve was linear (R² > 0.99) in the range of 0.1-1.5 mg/L, and the detection limits were 0.034 mg/L in deionized water and 0.082 mg/L in Sepang River water. Although these limits are not suitable for environmental analysis down to the parts per billion level, the water samples were first concentrated using a solid phase extraction column based on a biosorbent to enhance sensitivity by about a hundredfold. There were significant matrix effects, but robust sample preparation was used to reduce them. The concentrations of MG varied during the day and were highest at midday, which might have been because of higher aquaculture or industry activity at that time. Even though the levels were below the recommended limits for aquaculture products, the existence of MG is hazardous to the environment and human health because of its carcinogenic and mutagenic activities, especially in sensitive organisms.